A Computer-Based Simulation Showing Balance of the Population of Predator and Prey and the Effects of Human Intervention. Issue 1 (January 2021) - Kumar, Ankit; Jani, Kunal; Khatri, Divyansh; Patel, Hrishitva; Sharma, Aditya Kumar; Sahu, Nabin Kumar
Abstract: In this paper, a computer-based simulation of the predator-prey model has been proposed. The prey is a source of food for the predator, which is necessary for the prey's survival. Various models, such as the Lotka-Volterra model and the cellular automata model, have been used to simulate predator and prey movement in a population. These methods have been discussed briefly. The limitations of both these methods have been highlighted. After discussing the limitations of both these methods, a novel computer-based simulation has been proposed to address the previous models' limitations. Since this model takes into account a more realistic movement of predator and prey, it has been used to study the harmful effects of human intervention on the environment. In this simulation, the birth of predators and prey by mating, the death of predators and prey due to starvation, and the death of prey due to attacks from predators are taken into consideration. In the first case, there is no human intervention. In the next two cases, human intervention is taken into consideration. In one case, the proportion of predators in the population increases, and in the other case, the prey population increases. A comparison has been made between all three cases, and a study has been done showing how human intervention affects the population of predators and prey over a long time.